Dissecting Aneurysm of the L1 Radiculomedullary Artery Associated with Subarachnoid Hemorrhage: A Case Report - Crobeddu, Emanuela; Pilloni, Giulia; Zenga, Francesco; Cossandi, Christian; Garbossa, Diego; Lanotte, Michele (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Both spinal artery aneurysm and spinal subarachnoid hemorrhage represent a very rare event.Methods We report a case of a ruptured dissecting aneurysm of the right L1 radiculomedullary artery associated with subarachnoid hemorrhage and severe motor weakness.Results An urgent decompressive hemilaminectomy was performed due to worsening in motor deficit. A subsequent spinal angiography showed a dissection of radiculomedullary artery of L1 on the right side, treated conservatively.Conclusion Nowadays, therapeutic strategies for this aneurysm remain controversial. Conservative strategy can represent a valid alternative.
Keywords: subarachnoid hemorrhage; dissection aneurysm; radiculomedullary artery; conservative treatment